Characterisation of heat and mass transfer in the rectangular flat-sheet polyvinylidene flouride membrane for vacuum membrane distillation - Chiam, Chel Ken (2014)
This thesis presents a study of the heat and mass transfer performance in a laboratory-scale vacuum membrane distillation (VMD) process by using a rectangular cross-flow flat-sheet membrane module. One type of commercial polyvinylidene fluoride membrane with a nominal pore size of 0.2 μm and an effective area of 71.4 cm2 is tested. Results show that the traditional Nusselt and Sherwood correlations, which are frequently employed in the membrane distillation literature, are not suitably used to estimate the heat and mass transfer coefficients in the VMD system for Reynolds numbers ranging from 150 to 1400. By using distilled water as the feed solution, a new semi-empirical heat transfer correlation by suggesting Knudsen-viscous mechanism governs the water vapour transport across the membrane is developed. Compared to the feed flow rate, the feed temperature is the limit to the heat transfer. The heat transfer coefficients are strongly dependent on the physical properties of the feed solution, but less relied on the design of the membrane module. A semi-empirical mass transfer correlation is derived based on the analogy between heat and mass transfer. In a desalination experiment, it was observed that approximately 30% of the experimental data fit well with the semi-empirical Nusselt and Sherwood correlations. The heat transfer process is limited by the resistances in the feed boundary layer and the membrane. The heat transfer resistance in the membrane increases when that in the feed boundary layer decreases and vice versa. More than 50% of the heat transfer resistances occur in the liquid feed phase at feed flow rates below 1200 mL/min, whereas the remaining occur in the membrane itself. At feed flow rates that exceed 1200 mL/min, the heat transfer resistance in the membrane becomes dominant. The Knudsen-viscous resistance controls the mass transfer through the membrane while the mass transfer resistance in the liquid feed phase is absent. The membrane deformed during the VMD operation as the result of the external pressure that originated from the hydraulic pressure of the feed solution and the vacuum pressure acts on the membrane downwardly. It was noticed that the dimples stamped on the membrane surface by the perforation of the support do not significantly affect the heat and mass transfer performance during VMD. The deformed membrane with the dimpled surface is compacted. The permeability of the deformed membrane is enhanced from 3 to 20% by the compaction as a result of the membrane thickness reduction. Nusselt and Sherwood correlations that consider membrane deformation are developed to predict the flux through the deformed membrane. The differences between the fluxes calculated using the correlations with membrane deformation effects and the correlations without membrane deformation effects are generally less than 9%, suggesting that membrane deformation due to the membrane permeability enhancement may exert no significant influence on the performance of VMD.